X-linked Malformation and Cochlear Implantation. Issue 1 (January 2017) - Smeds, Henrik; Wales, Jeremy; Asp, Filip; Löfkvist, Ulrika; Falahat, Babak; Anderlid, Britt-Marie; Anmyr, Lena; Karltorp, Eva
Abstract : Objective: To evaluate if cochlear implantation is safe and constitutes an option for hearing rehabilitation of children with x-linked inner ear malformation. Study Design: Retrospective patient review in combination with a multidisciplinary follow-up. Setting: Tertiary referral hospital and cochlear implant program. Patients: Ten children with severe-profound mixed hearing loss and radiological findings consistent with Incomplete Partition type 3 cochlear malformation received cochlear implants during the years 2007 to 2015. Nine of the children had a mutation affecting the gene POU3F4 on Xq21. Intervention: Cochlear implantation. Main Outcome Measures: Surgical events, intraoperative measures and electrical stimulation levels, hearing and spoken language abilities. Results: In all, 15 cochlear implantations were performed. In three cases the electrode was found to be in the internal auditory canal on intraoperative x-ray and repositioned successfully. One child had a postoperative rhinorrhea confirmed to be cerebrospinal fluid but this resolved on conservative treatment. No severe complications occurred. Postoperative electrical stimulation levels were higher in 9 of 10 children, as compared with typically reported average levels in patients with a normal cochlea. Eight patients developed spoken language to various degrees while two were still at precommunication level. However, speech recognition scores were lower than average pediatric cases. Conclusion: Cochlear implantation is a safe procedure for children with severe-profound mixed hearing loss related to POU3F4 mutation inner ear malformation. The children develop hearing and spoken language but outcome is below average for pediatric CI recipients.